Minerals in the diet of adolescents aged 15 - Waksmańska, Wioletta; Woś, Halina; Łukasik, Renata; Bobiński, Rafał; Pielesz, Anna (Journal of Medical Science, 2018)
Introduction. Studies which focus on the supply of minerals in the diet of adolescents show that the diet is deficient in such macroelements as calcium and magnesium and such microelements as copper, zinc, iodine and iron. Inadequate supply of minerals may increase the risk of development of diet related diseases at a mature age.Material and Methods. The questionnaire on the consumption of food products consumed every day for the period of 7 days was filled in by the person conducting the survey. The needs for minerals were defined individually for every child with reference to recommended dietary allowance. Results. The norm of daily sodium intake among 15-year‑old adolescents was exceeded in all tested groups, however, in the group of boys sodium intake was at a higher level than in the group of girls. Potassium intake in the group of both girls and boys did not reach the recommended daily value, whereas the recommended daily consumption of manganese was exceeded twice. In all tested subjects, the ratio of calcium to phosphorus was very low. In the group of girls who are underweight, daily consumption of iron did not cover 50% of the demand.Conclusions. Inadequate supply of minerals recorded in all tested 15-year old subjects, regardless of their BMI, may lead to developmental disorders and diet related diseases at a mature age.